Partnerstwo w międzykulturowych małżeństwach mieszanych - Jodłowska, Małgorzata (Wydawnictwo Naukowe UAM, 2001)
Partnership in the contemporary world is a need and a necessity. But to define what it is in its essence and to what extent its realization is possible, especially in the multicultural mixed marriages is the main question of this article that the author is going to give answer to. The relationships that interest the author the most are those in which one of the partners has Polish background, while the other has a non-European background (Asian or African). The author analyzes the various definitions of partnerships made by spouses of Polish and foreign background, their own ways o f assessing marriage based on partnership (or not) and also the extent of its realization in two zones: institutional-functional and, in some aspects, the personal zone. The first zone includes those issues concerning a fair share of house duties, right to make main decisions about marital/ family life and women’s professional life. The second one is about open honest communication between the spouses. The author also tries to define some of the factors, which may be or may not be conducive to the realization of partnership in the relationships of her research.
The partnership in multicultural mixed marriages